Correlation between Malocclusions, Tonsillar Grading and Mallampati Modified Scale: A Retrospective Observational Study - Can Serif Kuskonmaz; Giovanni Bruno; Maria Lavinia Bartolucci; Michele Basilicata; Antonio Gracco; Alberto De Stefani (MDPI AG, 2023)
Aim: to investigate the correlation between growth tendency and different patient malocclusion, tonsillar grading, and tongue size (Mallampati index). Materials and Methods: The sample is composed of 64 males and 40 females; patients aged between 6 and 16 years (median age 11 years, IQR 9-13) were included. The final sample is therefore 104 patients. After the first orthodontic visit, all the children underwent a collection of documentation (photographs, digital arch models, and X-rays). Patients were classified according to their malocclusion, palatal conformation, tonsillar grading, and Mallampati index. Group comparisons were performed using Fisher's test. A p-value less than 0.05 was considered statistically significant. Results: The narrow palate was more frequent in those with Angle class III (p = 0.04), while the other variables considered (tonsillar grading, Mallampati, and lingual frenulum) were not significantly associated with dental class (p > 0.05). Furthermore, a different distribution of tonsillar grading was observed between subjects with normal palate and subjects with narrow palate, while no statistically significant association was found between the palatal shape and Mallampati index (p = 0.88). Conclusions: This study found that children with higher tonsillar grading had a higher prevalence of crossbite or narrow palate compared to other children at the same developmental stage. However, we did not observe any association between tonsil hyperplasia and the prevalence of class II malocclusion, anterior open bite, or patient divergence in this sample. Furthermore, no correlation was found between the Mallampati index and patients' dental class, narrow palate, or divergence in this study.